Analyzing primary Hodgkin and Reed-Sternberg cells to capture the molecular and cellular pathogenesis of classical Hodgkin lymphoma - Tiacci, Enrico; Mechtersheimer, Gunhild (Blood, 2012)
The pathogenesis of classical Hodgkin lymphoma (cHL), the most common lymphoma in the young, is still enigmatic, largely because its Hodgkin and Reed-Sternberg (HRS) tumor cells are rare in the involved lymph node and therefore difficult to analyze. Here, by overcoming this technical challenge and performing, for the first time, a genome-wide transcriptional analysis of microdissected HRS cells compared with other B-cell lymphomas, cHL lines, and normal B-cell subsets, we show that they differ extensively from the usually studied cHL cell lines, that the lost B-cell identity of cHLs is not linked to the acquisition of a plasma cell-like gene expression program, and that Epstein-Barr virus infection of HRS cells has a minor transcriptional influence on the established cHL clone. Moreover, although cHL appears a distinct lymphoma entity overall, HRS cells of its histologic subtypes diverged in their similarity to other related lymphomas. Unexpectedly, we identified 2 molecular subgroups of cHL associated with differential strengths of the transcription factor activity of the NOTCH1, MYC, and IRF4 proto-oncogenes. Finally, HRS cells display deregulated expression of several genes potentially highly relevant to lymphoma pathogenesis, including silencing of the apoptosis-inducer BIK and of INPP5D, an inhibitor of the PI3K-driven oncogenic pathway.